Creative thinking skills in science learning using the RADEC learning model - Syifa Putri Agustin, Nur; Ramadhan Firdaus, Anugrah; Kelana, Jajang Bayu (Current Issues on Elementary Education Journal, 2023)
The creative thinking skills of Indonesian citizens are ranked 115th out of 139 countries, meaning that the creative thinking skills of the Indonesian state are low. This needs to be overcome by giving treatment to everyone, one of which is through education. The research conducted aims to determine creative thinking skills in science learning for class V SD by applying the Read; Answer; Discuss; Explain and Create (RADEC) learning models. In this study, the researcher used qualitative methods with a population of fifth grades at elementary school Cisarua areas and a samples of 31. The results showed that fifth grade students had difficulties in improving creative thinking skills on indicators of fluent thinking and elaboration skills, but this can be overcome by applying them. RADEC learning model. The application of the RADEC learning model produces a positive response to science learning in improving creative thinking skills